(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the vectors of the foreign policy of the Republic of Uzbekistan. Attention is paid to the political and legal foundations of the Republic’s foreign policy, statistical data, and documentary foundations of foreign policy. The article also analyzes the interest of the leadership of the Republic of Uzbekistan in strengthening ties with the countries of Central Asia through cooperation in overcoming common security threats (the drying up of the Aral Sea, terrorism, religious conflicts, the penetration of drugs and weapons, the factor of tension in relations with Afghanistan), in issues of migration and customs policy.